Distorsi Pesan Dalam Komunikasi Organisasi Kajian Teoritis Terhadap Kesalahan Ketik Penetapan Ketua KPU RI Sebagai Tersangka Oleh Kepolisian Republik Indonesia - Bachruddin Ali Akhmad (Balai Pengembangan SDM dan Penelitian Komunikasi dan Informatika (BPSDMP Kominfo) Banjarmasin, 2014)
“Typo” as the reason that have been proposed by the police of republic Indonesia to abrogate the suspect status of chairman of the election commission (KPU) to witness reported, could not be accepted by some members of the citizens. However in depth research the judge from the citizens are have much biases. Otherwise, legally formal, the reason of the abrogate has been confirmed, both from substantive or in terms of the law. because the act of